(untitled) (Western Journal of Medical and Biomedical Sciences, 2024)
The unlimited access and availability of free information provided by the internet has resulted in the frequent search for health information by patients to obtain first opinion on health issues ahead of encounter with the doctor. The study assessed the prevalence of the use of internet to seek for health information and to determine the association between the online search for health information andsociodemographic characteristics of patients. It was a cross sectional study conducted at the Family Medicine Clinic of Delta State University Teaching Hospital, Oghara,Nigeria.Participants were recruited using systematic random sampling method. An interviewer administered questionnaire was used to obtain data. Data was analyzed using Statistical Product and Service Solution version 22 (IBM, Chicago). The level of significance of analysis was set at p < 0.05 and ethical approval was obtained. Participants recruited were aged 18 years and above. The mean age was 43.42 ± 15.33, with 54.2% within the age range of 18 to 44 years. There were more females (60.0%) than males (40.0%). The prevalence of internet use to seek health information was 44.9%, 75.2% searched for disease related information and 93.0% used Google search engine. There was statistically significant association between the use of internet for health information and age, marital status, place of residence, level of education and the presence of chronic illness. The study showed an increase in the use of internet for health information and recommend the need for stakeholders to focus on repositioning the healthcare information dissemination channels.